ANALISIS PUTUSAN NO.178/Pid Sus/2018/PN MR TERHADAP KASUS PENGGUNA NARKOTIKA DI PENGADILAN NEGERI MOJOKERTO - Siswandi, Lambang; Suhartono, Slamet; Herlin Setyorini, Erny (Yayasan Akrab Pekanbaru, 2019)
Narcotics is a serious Nation problem and must be resolved immediately by the state and government. Considering that narcotics users are increasingly difficult to overcome, and most of the users are teenagers, so analyzing a study (Case Study) is needed. This study aims to understand and analyze the results of decision No.178 / Pid Sus / 2018 / PN MR against narcotics users in the Mojokerto District Court. The method used in this study uses normative legal research methods to test so that there is a theoretical relevance to the research methods needed. The approach taken by researchers is the Normative Approach and the Concept Theory Approach. Adjusting to the scope and identification of the problems that exist in this study, researchers used Primary Legal Materials obtained directly from the object of field research on the results of decision No. 178 / Pid Sus / 2018 / PN MR in the Mojokerto District Court, law books, Law no. 35 of 2009, the Criminal Code and the Criminal Procedure Code, Secondary legal material in the form of literature and Tertiary studies as a guide and explanation of Primary and Secondary legal sources. After conducting research it was found that the decision No.178 / Pid Sus / 2018 / PN MR which was decided by the judge against narcotics users with the weight of evidence less than 1 gram should be rehabilitated instead of being convicted.